جدلية الفحولة والأنوثة في الخطاب النقدي عند الغذامي - الشاوي, عبد القادر; شعيب, إبراهيم (جامعة الوادي - University of Eloued, 2023)
يحاول هذا المقال تَتَبُّعَ ثنائِيَّةٍ مِنْ أَهَمِّ الثُّنَائِيَّات في الثَّقافة لدى الغذامي، وهو ناقدٌ عربيٌّ معاصر، بذل جهودا كبيرةً لكشفِ عيوبِ الثَّقَافّةِ العَرَبِيَّةِ، من خلال قراءةٍ مختلفة ومغايرة لمنجزاتِ التراثِ العربي في القديم و الحديث. وهذه الثُّنَائِيَّة هي: ثنائية الفحولة/الأنوثة، وذلك من خلال أهمِّ مُؤَلَّفَاتِهِ التي عُنِيَتْ بالمرأة وقضايا اللُّغَةِ و الإبداع النِّسوي، للوصول إلى موقف هذا الناقد من جهة، و من جهة أخرى للوصول إلى قراءة جديدة لهذه الثُّنائِيَّة التي تُعَدُّ إشكاليَّةً مِحْوَرِيَّةً في أَغْلَبِ دِراساتِهِ النَّقْدِيَّة، خاصَّة في إطار مَشْرُوعِهِ النَّقْدِيِّ الجَدِيدِ، تَحْتَ مُسَمَّى النَّقْد الثَّقَافِيّ . This article attempts to trace one of the most important dualities in Arab culture among Al-Ghadhami, a contemporary Arab critic, who made great efforts to uncover the defects of Arab heritage, through a different and contrasted reading of the achievements of Arab culture, in ancient and modern times. And this dualism is: the duality of virility / femininity, through his most important works on women and issues of language and feminist creativity, to reach the position of this critic on the one hand, and on the other hand to reach a new reading of this dualism, which is considered to be a pivotal problematic in the sense of His critical studies, especially within the framework of his new critical project, under the name of cultural criticism.
Keywords: المرأة ; الفحولة ; الأنوثة ; النقد ; النقد الثقافي ; الغذامي; Woman ; Virility ; Femininity ; criticism ; Cultural Criticism ; Al-Ghadhami